Analysis of Lecturers' and Students' Perceptions of Teaching Practitioner Programs in Higher Education - Mukhtar Galib; Ulfa Dwiyanti; Andi Batary Ciita (Postgraduate, University of Mataram, 2023)
The splendor of Freedom of Learning in the educational environment and Indonesian society is visible, among the various programs there is one program that is relevant to students and industry, namely the Teaching Practitioner program. This research aims to analyze the perceptions of lecturers and students regarding implementing the Teaching Practitioner Program in Higher Education in the city of Makassar. Students, as the nation's successors who are expected to be agents of change, are required to have the ability to compete in the world of work in the future. The research method used is quantitative descriptive with a random sampling technique based on cluster areas, to select lecturers and students who have participated in the program. Of the 200 questionnaires distributed, 150 respondents responded, consisting of 25 lecturers and 125 students. The research results show that the Teaching Practitioner Program at Makassar City University has positive aspects in improving the quality of learning for students and graduates, reducing the potential for unemployment, providing a dynamic learning experience, encouraging collaboration with industry, and ensuring the suitability of competencies to the needs of the world of work. This research contributes to understanding the importance of integrating education and the world of work through the Teaching Practitioner Program in higher education